Highly electro‐responsive composite gel based on functionally tuned graphene filled polyvinyl chloride. (20th May 2021) - Ali, Imdad; Ali, Ahsan; Ali, Ahmed; Ramzan, Muhammad; Hussain, Khalid; Xudong, Li; Jin, Zhan; Titton Dias, Otavio Augusto; Weimin, Yang; Haoyi, Li; Liyan, Zhang; Sain, Mohini
Abstract: Electroresponsive devices have attended significant interest for actuators and artificial muscles in recent days but are susceptible to low deformation at applied voltages. To address this problem, herein, we have prepared novel flexible composite gel based on polyvinyl chloride (PVC), dibutyl adipate (DBA), and functionalized reduced graphene oxide (f‐rGO) via solution casting technique. The structural, morphological, optical, mechanical, and thermal properties of the composite PVC/f‐rGO gel were characterized by using various techniques. In order to test the usefulness of PVC/f‐rGO, we fabricated the new planar PVC/f‐rGO‐based gel actuator, by holding the gel between two electrodes. Stimuli‐responsive deformation of ~2.7 mm was measured at a voltage of 1200 V for an optimized gel in the designed device. The loading of silane‐f‐rGO greatly enhanced the stimulation, response time and flexibility of the PVC gel. The highest elongation at break of about 433% was achieved for f‐rGO‐loaded PVC gel owing to strong dipole–diploe interactions between alpha hydrogen of PVC and ‐NH2 of f‐rGO. We believe that highly electro‐stimulated, soft and, flexible PVC/f‐rGO gels could open a new avenue for the fabrication of advanced artificial muscles and tunable soft actuators for number of applications.